Multi-Voiced Music Bypasses Attentional Limitations in the Brain - Barrett, Karen Chan; Ashley, Richard; Strait, Dana L.; Skoe, Erika; Limb, Charles J.; Kraus, Nina (Frontiers in Neuroscience, 2021)
Attentional limits make it difficult to comprehend concurrent speech streams. However, multiple musical streams are processed comparatively easily. Coherence may be a key difference between music and stimuli like speech, which does not rely on the integration of multiple streams for comprehension. The musical organization between melodies in a composition may provide a cognitive scaffold to overcome attentional limitations when perceiving multiple lines of music concurrently. We investigated how listeners attend to multi-voiced music, examining biological indices associated with processing structured versus unstructured music. We predicted that musical structure provides coherence across distinct musical lines, allowing listeners to attend to simultaneous melodies, and that a lack of organization causes simultaneous melodies to be heard as separate streams. Musician participants attended to melodies in a Coherent music condition featuring flute duets and a Jumbled condition where those duets were manipulated to eliminate coherence between the parts. Auditory-evoked cortical potentials were collected to a tone probe. Analysis focused on the N100 response which is primarily generated within the auditory cortex and is larger for attended versus ignored stimuli. Results suggest that participants did not attend to one line over the other when listening to Coherent music, instead perceptually integrating the streams. Yet, for the Jumbled music, effects indicate that participants attended to one line while ignoring the other, abandoning their integration. Our findings lend support for the theory that musical organization aids attention when perceiving multi-voiced music.